Determinants of Financial Rewards from Industry-University Collaboration in South Korea - Junghee Han; Almas Heshmati (Institute for the Study of Labor (IZA), 2013)
The external circumstances for universities have been changing rapidly. In order to be competitive, survive, and flourish, universities have shown a growing enthusiasm to generate financial revenues externally. The literature refers to this phenomenon as academic capitalism, defined as the involvement of colleges and faculties in market-like behaviors, which has become a key feature of higher education finances in most countries. As a result, technology transfer, technology commercialization, and patents awarded via industry-university collaboration represent a source of financial rewards. This paper explores the determinants of financial rewards of universities sources from industry-university collaboration in South Korea. We find that among the determinants of financial performances, technology transfer per employee working at technology licensing offices, participation of engineering faculty, patent approvals, the volume of research funds, the number of employees, and firms in incubators within universities turn out to be significant contributors to externally sourced university revenues. Technology commercialization using technology transfer and incentive rules for developers are not statistically significant. In the light of these findings, it appears that an industry-university cooperation foundation program is likely to play a strong role in private university finances in Korea.
Keywords: A20; D45; I22; L24; P12; 330; industry-university collaboration; entrepreneurial university; university revenues; South Korea